Investigation of the Pro-active Role of Alpha Amyrin Nanoemulsions in Quashing Neurodegeneration, Excitotoxicity, and Neuronal Inflammation-A Combined in vivo and in silico Approach - Baburaj, Ratna; V, Rajendra Sandur; Das, Kuntal (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: Aluminium is a pervading metal that poses a serious threat causing severe brain damage and neuro-degeneration. Alpha amyrin a pentacyclic triterpene despite its potency has not been properly utilized to treat neurodegenerative disorders because of its erratic GI absorption and poor BBB permeability. Purpose: To determine the role of alpha amyrin nano-emulsion in neuroinflammation induced by aluminium through an in vivo and in silico approach. Materials and Methods: An in silico approach was opted to determine the possible interactions of the drug with various inflammatory markers and was performed using Autodock. A chitosan-decorated nano-emulsion of alpha amyrin was prepared, characterized, and administered intranasally to Wistar albino rats for 42 days. The role of the treatment on neuroinflammation was measured by checking levels of SOD, catalase, inflammatory markers like IL-6, TNF-α, and acetylcholine esterase, and glutamate levels in the brain. Also, histopathology studies were performed in detail. Results: The results confirm that alpha amyrin interacts well with the inflammatory markers with a good docking score, thereby inhibiting them. The administration of nano-emulsion brings about improvement in the anti-oxidant status of the brain, reduction in neuroinflammatory markers, and acetylcholine esterase levels in rat brains. Histopathology of rat brains shows that alpha amyrin nano-emulsion administration brought about neuro-protection as it increased the number of intact neurons, and lowered neuronal damage, gliosis and pyknosis brought about by aluminium. Conclusion: The results and findings confirm the pro-active role of alpha amyrin nano-emulsion in quashing neuro-degeneration and neuro-inflammation in aluminum-induced neuro-toxicity.
Keywords: Aluminium; Alpha amyrin; Neuro-toxicity; Inflammatory markers; Nano-emulsion; Docking; Neuro-protection